Applications of Symmetry Methods to the Theory of Plasma Physics - Cicogna, G.; Ceccherini, F.; Pegoraro, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The theory of plasma physics offers a number of nontrivial examples of partial differential equations, which can be successfully treated with symmetry methods. We propose three different examples which may illustrate the reciprocal advantage of this "interaction" between plasma physics and symmetry techniques. The examples include, in particular, the complete symmetry analysis of system of two PDE's, with the determination of some conditional and partial symmetries, the construction of group-invariant solutions, and the symmetry classification of a nonlinear PDE.